17β-Estradiol Inhibits PCSK9-Mediated LDLR Degradation Through GPER/PLC Activation in HepG2 Cells - Fu, Wei; Gao, Xiao-Ping; Zhang, Sheng; Dai, Yan-Ping; Zou, Wen-Jun; Yue, Li-Min (Frontiers in Endocrinology, 2020)
Plasma levels of PCSK9 are significantly higher in postmenopausal women. Pharmacologically increased estrogen levels have been shown to lower PCSK9 and LDL-C levels in animals and humans. The action of estrogens suggests that it has the ability to prevent PCSK9-mediated LDLR degradation in liver cells. However, little is known about how estrogen alters PCSK9-mediated LDLR degradation. Here, we report that 17β-estradiol (βE2) reduces PCSK9-mediated LDLR degradation by a mechanism that involves activation of G protein-coupled estrogen receptor (GPER). In cultured HepG2 cells, βE2 prevented the internalization of PCSK9 which subsequently lead to PCSK9-mediated LDLR degradation. The altered LDLR levels also resulted in an increase in LDL uptake that was not observed in the absence of PCSK9. In addition, we showed that clathrin was rapidly increased in the presence of PCSK9, and this increase was blocked by βE2 incubation, suggesting rapid recruitment of clathrin in HepG2 cells. PLCγ activation and intracellular Ca2+ release were also increased due to the rapid effect of estrogen. By using a GPER antagonist G15, we demonstrated that GPER mediates the action of estrogen. Together, the data from this in vitro study demonstrate that estrogen can regulate LDLR levels mainly through GPER activation, which prevents PCSK9-dependent LDLR degradation in HepG2 cells.